Computational and experimental approaches to explore defense related enzymes conferring resistance in Fusarium infected chilli plants by regulating plant metabolism through nutritional products - Muhammad Usman; Muhammad Atiq; Nasir Ahmed Rajput; Muhammad Sagheer; Ye Xia (PLoS ONE, 2025)
Nutritional status being the first line of defense for host plants, determines their susceptibility or resistance against invading pathogens. In recent years, the applications of plant nutrient related products have been documented as one of the best performers and considered as alternatives or/and supplements in plant disease management compared to traditional chemicals. However, knowledge about application of plant nutrient related products for the management of destructive fungal pathogen Fusarium oxysporum f.sp. capsici and their impact on the components of the antioxidant defense system, especially in chilli plants, still needs to be discovered. Therefore, in this current study, we aimed to evaluate two nutrient fertilizers viz. Krystafeed and Micro Plus at three different concentrations by soil drenching method for their effects against the Fusarium wilt of chilli and investigate the components of the antioxidant defense system of chilli plants. Correlation and computational analysis on the components of antioxidant defense system in various pathways were performed to predict the suitable binding sites of mineral ions. Results indicated that the combination of Krystafeed and Micro Plus was found the most effective with (27.01, 26.59%) disease incidence, followed by Micro Plus (29.56, 32.35%) and Krystafeed (38.21, 41.15%), both in greenhouse and field conditions, respectively. Moreover, the combination of Krystafeed and Micro Plus significantly increased the concentration of SOD (27.53, 108.96)%, POD (37.29, 45.65)%, CAT (19.33, 95.33)%, H2O2 (22.13, 118.98)%, TPC (27.39, 17.37)%, chlorophyll a (21.80, 35.74)%, chlorophyll b (57.57, 18.25)%, total chlorophyll (30.21, 19.83)%, Tocopherol (13.08, 33.66)%, TrxR (5.03, 36.56)%, MDA (13.84, 54.79)%, ascorbate (4.72, 17.28)%, Proline (5.94, 59.31)%, and phytoalexin (Capsidiol) (11.33, 55.08)% in the treated plants of resistant and susceptible chilli varieties, respectively, as compared to the untreated plants. Pearson’s correlation heat-map analysis showed that all the enzymes of antioxidant defense system were found positively correlated with each other. It is concluded that the improvement of crop resistance by the application of plant nutrient related products may be viable alternatives to synthetic chemicals for managing Fusarium wilt disease of chilli and potentially other pathogens.